2015
DOI: 10.1186/s12887-015-0416-6
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial meningitis in children under 15 years of age in Nepal

Abstract: BackgroundBacterial meningitis in children is a life-threatening problem resulting in severe morbidity and mortality. For the prompt initiation of antibacterial therapy, rapid and reliable diagnostic methods are of utmost importance. Therefore, this study was designed to find out the rate of bacterial pathogens of meningitis from suspected cases by performing conventional methods and latex agglutination.MethodsA descriptive type of study was carried out from May 2012 to April 2013. Cerebrospinal fluid (CSF) sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
40
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 41 publications
(36 reference statements)
10
40
2
3
Order By: Relevance
“…1,9,21 The mortality rate was 11% and it was found most commonly in early paediatric age group (0 -2 years) as compared with others studies as shown in Table 4. 16,22,23 …”
mentioning
confidence: 99%
“…1,9,21 The mortality rate was 11% and it was found most commonly in early paediatric age group (0 -2 years) as compared with others studies as shown in Table 4. 16,22,23 …”
mentioning
confidence: 99%
“…En yaygın olan bakteriyel menenjit etkenlerinin antijenlerinin belirlenmesinde LAT'ın duyarlılı-ğının %50-100 arasında değiştiği bildirilmektedir (8) . Yadhav (29) yaptığı çalışmaya beş yaş altı klinik şüpheli 100 çocuğu dâhil etmiş, akut bakteriyel menenjit tanısı alan olguların (n=24) 21 (%87.5)'inin kültür ile, 17 (%70.8)'sinin Gram boyama ile, sekizinin (%33.3) LAT ile pozitif olduğunu, Gram boyama ve LAT'ın birlikte değerlendirildiğinde, olguların %85'inin tespit edildiğini belirtmiştir.…”
Section: Discussionunclassified
“…Bakteriyel menenjitin etiyolojik tanısı bir saatten daha kısa sürede sonuç-lanan Lateks Aglütinasyon Testi (LAT) ile müm-kün olabilmektedir (8) . Bu test bakteriyel menenjitin hızlı tanısında %50-100 arasında değişen duyarlılığa sahiptir.…”
Section: Introductionunclassified
“…It has been reported secondary to trauma or neurosurgery, but also as a spontaneous illness 8, 9. E. coli is a frequent pathogen in pediatric bacterial meningitis 1 but is rare in adult forms of the disease 2, 3, 4. E. coli may cause infections of the bloodstream, urinary tract, biliary system, and peritoneal space.…”
Section: Discussionmentioning
confidence: 99%
“…coli ) is a frequent pathogen in pediatric bacterial meningitis 1, but is rare in adult forms of the disease 2, 3, 4. In general, acute bacterial meningitis is diagnosed based on clinical signs and cerebrospinal fluid (CSF) analysis.…”
Section: Introductionmentioning
confidence: 99%